The oyster Crassostrea gigas (Thunberg 1795) culture in an artisanal breeding pond, La Arena, Casma. - Baltazar, Paul (1999)
This paper describes the methodology used for the culture of Pacific oyster Crassostrea gigas in an artisanal breeding pond in the La Arena acuicola center, in Casma. Reproducers at gonadal maturity phase from the culture lines of the center were used. They were prepared in fiber glass tanksi of 1000 L capacity with unfiltered sea water at 27 ± 0,9 oC, and fed with maize fecula and microalgae collected from site. In one group spawning was induced by thermal stimulation (30 to 31 oC), in the other one hydrogen peroxide was added, obtaining different responses. 20 minutes after fertilization the polar body was defined in 100% of fertilized eggs; veliger larvae were visible 24 hours after fertilization. Larvae reached the pediveliger stage 20 days after culture, with average sizes of 237 ± 10 µm. Ground shells (300pm), sandpapered black plastic and oyster valvas were used for settlement of larvae. To the 33rd day, larva seeds had an average size of 1262 ± 204 µm. Then, they were introduced in pearl net for development in the sea. 30 days after sowing larvae in the sea, the average length of postlarvae was 13,4 ± 3,4 mm. This work showed the benefits of this methodology in the massive production of seeds in an artisan breeding pond.